Integrated modelling of toroidal rotation with the 3D non-local drift-kinetic code and boundary models for JT-60U analyses and predictive simulations. (26th June 2015) - Honda, M.; Satake, S.; Suzuki, Y.; Yoshida, M.; Hayashi, N.; Kamiya, K.; Matsuyama, A.; Shinohara, K.; Matsunaga, G.; Nakata, M.; Ide, S.; Urano, H.
Abstract: The integrated simulation framework for toroidal momentum transport is developed, which self-consistently calculates the neoclassical toroidal viscosity (NTV), the radial electric field and the resultant toroidal rotation together with the scrape-off-layer (SOL) physics-based boundary model. The coupling of three codes, the 1.5D transport code TOPICS, the three-dimensional (3D) equilibrium code VMEC and the 3D drift-kinetic equation solver FORTEC-3D, makes it possible to calculate the NTV due to the non-axisymmetric perturbed magnetic field caused by toroidal field coils. Analyses reveal that the NTV significantly influences in JT-60U and holds the key to determine the NTV profile. The sensitivity of the profile to the boundary rotation necessitates a boundary condition modelling for toroidal momentum. Owing to the high-resolution measurement system in JT-60U, the gradient is found to be virtually zero at the separatrix regardless of toroidal rotation velocities. Focusing on, the boundary model of toroidal momentum is developed in conjunction with the SOL/divertor plasma code D5PM. This modelling realizes self-consistent predictive simulations for operation scenario development in ITER.